The Nationalism of Educators: A Case Study of the Nationalistic Insights of Teachers of MAN Cirebon Regency - Noval Maliki; Hilyatul Auliya; Badawi Murai; Lukman Hakim; Karyono Karyono (Jurnal Penelitian, 2022)
In this piece, the nationality of the Madrasah Aliyah Negeri (MAN) instructors in the Cirebon district is attempted to be captured. It is believed that some people's understanding of the national outlook has been compromised by the rapid flow of information and the waning of nationalism as an ideology. Teachers have emerged as crucial circles for inquiry from many national viewpoints as educated circles and agents of knowledge and values to pupils. This study employed qualitative approaches as its methodology. The findings indicated that MAN teachers in the Cirebon district had a very high nationality insight. In contrast, a teacher revealed in an interview that he was unfamiliar with the idea of the caliphate, which had been used to criticize the democratic system.